The BabyView camera: Designing a new head-mounted camera to capture children’s early social and visual environments - Long, Bria; Goodin, Sarah; Kachergis, George; Marchman, Virginia A.; Radwan, Samaher F.; Sparks, Robert Z.; Xiang, Violet; Zhuang, Chengxu; Hsu, Oliver; Newman, Brett; Yamins, Daniel L. K.; Frank, Michael C. (Behavior research methods, 2024)
Head-mounted cameras have been used in developmental psychology research for more than a decade to provide a rich and comprehensive view of what infants see during their everyday experiences. However, variation between these devices has limited the field’s ability to compare results across studies and across labs. Further, the video data captured by these cameras to date has been relatively low-resolution, limiting how well machine learning algorithms can operate over these rich video data. Here, we provide a well-tested and easily constructed design for a head-mounted camera assembly—the BabyView—developed in collaboration with Daylight Design, LLC., a professional product design firm. The BabyView collects high-resolution video, accelerometer, and gyroscope data from children approximately 6–30 months of age via a GoPro camera custom mounted on a soft child-safety helmet. The BabyView also captures a large, portrait-oriented vertical field-of-view that encompasses both children’s interactions with objects and with their social partners. We detail our protocols for video data management and for handling sensitive data from home environments. We also provide customizable materials for onboarding families with the BabyView. We hope that these materials will encourage the wide adoption of the BabyView, allowing the field to collect high-resolution data that can link children’s everyday environments with their learning outcomes.